Analisis Pengaruh Literasi Keuangan, Karakteristik Mahasiswa dan Lingkungan Kampus Terhadap Manajemen Keuangan Pribadi Mahasiswa - Yustina Maro; Sefnat Aristarkus Tang; Junius M. Sau Sabu (Peneliti.net, 2023)
Financial Management is an activity of planning, budgeting, and saving funds owned by an organization or company. This study aims to determine the effect of financial literacy, student characteristics, and the campus environment on student personal financial management with a sample of 54 people. Collecting data using observation, interviews, and questionnaires. Data analysis uses instrument tests, namely validity tests, and reliability tests; the classic assumption test is the normality test, multicollinearity test, heteroscedasticity test, and linearity test while the hypothesis testing uses multiple linear analysis namely the t-test and F test. The results show that partially financial literacy has a significant effect on student financial management as indicated by a significant t-test of 0.000. Partially the student characteristic variables have a significant effect on student financial management as indicated by. t test the significant value of 0.001. Partially, campus environment variables have a significant effect on student financial management as indicated by a significance value of the t-test of 0.000. Simultaneously the variables of financial literacy, student characteristics, and campus environment have a significant effect on student financial management as indicated by the significant value of the F test of 0.000.